Examining Healthcare Profesional’s Acceptance of Electronic Medical Records System using Extended UTAUT2 (Buana Information Technology and Computer Sciences (BIT and CS), 2024)
This study aims to analyze user acceptance of the Electronic Medical Record system using the extended Unified Theory of Acceptance and Use Technology 2 model at PKU Muhammadiyah Bantul hospital. The UTAUT 2 model was chosen because it is the latest technology acceptance model which is a unification, synthesis, or summary of the eight pre-existing technology acceptance models. The subjects in this study were PKU Muhammadiyah Bantul hospital employees who used an electronic medical record system specifically for outpatient care. The object of this study is user acceptance of using the RME system in health services. Data collection techniques in this study are using questionnaires and observation. This research is a type of quantitative analytic research with data analysis using descriptive analysis. Data processing in this study used Smart-PLS software version 4.0 with SEM-PLS data analysis. The results showed that the aspects of the extended UTAUT2 model that had a positive and significant effect on user acceptance were performance expectancy (t=1.816), while the aspects of effort expectancy (t=0.419), social influence (t=0.635), facilitating conditions (t=0.139), hedonic motivation (t=0.909), price value (t=.304) habit (t=1.458), trust (t=0.032) and perceived risk (1.365) have no effect on user acceptance of the EMR system. Gender and age moderation variables were found to have no effect on the relationship between variables.